ASEAN ECONOMIC COMMUNITY AND THE COMPETITIVENESS OF VIETNAM’S AGRICULTURAL SECTOR - Angga Bagus Bismoko (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2016)
In the last ten years, Vietnam has become an agricultural country to be reckoned with in the international market. However, the competitiveness of Vietnamese agricultural sector is still unstable, especially when compare to the Thailand in the long-run. Moreover, Vietnam has to fight with the implementation of AEC in full at the end of 2015 which implies the increasing levels of competition in Southeast Asia. Understanding the developments of Vietnam’s agriculture in the face of various challenges and opportunities through the implementation of AEC become the major purpose of this research. Qualitative methods used to analyze primary data were collected through indepth interview and several secondary data that has been collected. The results of this research shows that Vietnam face two major obstacles in producing agricultural commodities that safe and have high quality plus the low labor productivity. Nevertheless, the Government of Vietnam conducting several policies in improving the quality and safety of agricultural commodities such as the No Early Spray Campaign, 3G3R and 1M5R. Moreover, through the mechanism of the Public-Private Partnership (PPP), the Government of Vietnam strives to bridge the mutually beneficial cooperation between farmers and companies. In addition, the Government of Vietnam is trying to take benefits from the AEC to increase the flow of foreign investment to build its agricultural sector by providing various incentives for supporting potential investors.Keywords: AEC, competitiveness, the agricultural sector, Vietnam AbstrakDalam sepuluh tahun terakhir, Vietnam berhasil menjadi negara pertanian yang patut diperhitungkan dalam pasar internasional. Meskipun demikian, daya saing sektor pertanian Vietnam masih belum stabil dalam mengimbangi Thailand dalam jangka panjang. Lebih dari itu, Vietnam harus berjibaku dengan pengimplementasian MEA secara penuh di akhir 2015 dan berpotensi meningkatkan persaingan di kawasan Asia Tenggara. Memahami pembangunan daya saing pertanian Vietnam dalam menghadapi berbagai tantangan dan kesempatan di era MEA menjadi tujuan besar dari penelitian ini. Penelitian ini menggunakan metode penelitian kualitatif untuk menganalisis data primer hasil wawancara mendalam dan juga berbagai data sekunder yang telah dikumpulkan. Hasil penelitian menunjukkan bahwa hingga saat ini, Vietnam masih menghadapi kendala besar dalam menghasilkan komoditas pertanian yang aman dan berkualitas tinggi ditambah juga rendahnya produktivitas tenaga kerjanya. Meskipun demikian, Pemerintah Vietnam tengah melakukan berbagai kebijakan untuk meningkatkan kualitas dan keamanan komoditas pertanian antara lain melalui No Early Spray Campaign, 3G3R dan 1M5R. Lebih dari itu, melalui mekanisme Public-Private Partnership (PPP), Pemerintah Vietnam berupaya menjembatani kerjasama saling menguntungkan antara petani dengan perusahaan. Selain itu, Pemerintah Vietnam berupaya memanfaatkan MEA guna meningkatkan arus investasi luar negeri demi membangun sektor pertaniannya dengan menyediakan berbagai insentif bagi para calon investor.Kata kunci: MEA, daya saing, sektor pertanian, Vietnam.